AN INFLUENCE OF PARAMETER VARIATION ON MODEL-BASED EMERGENCY FORECASTIING IN THE PULSE SYSTEM - Kolokolov, Yury; Monovskaya, Anna (International Journal of Computing, 2014)
Practical realization of model-based emergency forecasting in pulse systems for the case of multi-parameter variation in a possible wide range associates with the problem of a-priori forming of single-statement information on system dynamics. The fractal diagram is proposed to use for the purpose of system dynamics presentation. This diagram allows one-to-one correspondence between the both, parameter and phase,spaces establishing by line up stages.